Study on the health status of sheep and goats and direct economic losses due to organs and carcass condemnation in Addis Ababa Municipal Abattoir Enterprise, Ethiopia - Bekele, T.; Szonyi, Barbara (International Livestock Research Institute, 2014)
A study was conducted at Addis Ababa Municipal Abattoir Enterprises (AAMAE) in Addis Ababa, Ethiopia with the following objectives: 1) to assess the health status of sheep and goats presented for slaughter to AAMAE, 2) to identify the most common causes of organ and carcass condemnation in sheep and goats slaughtered at AAMAE, and 3) to estimate the magnitude of direct economic loss attributed to the condemnation of organs and carcasses at AAMAE. A cross-sectional study which involved both ante-mortem and post-mortem examinations was conducted on 768 small ruminants (384 sheep and 384 goats) from January 2014 to July 2014. Study animals were selected through systematic random sampling. During ante-mortem examination, skin disorders, poor body condition, and respiratory disorders were the most common abnormalities encountered. Postmortem examination revealed that 5 (0.7%) hearts, 233 (30%) lungs, 264 (34%) livers, 4 (0.5%) kidneys and 2 (2%) carcasses were condemned due to various causes. Pericarditis and hydropericardium were the causes of heart rejection. The main causes of lung condemnation were pneumonia and hydatid cysts. Fasciolosis was the main cause of liver condemnation followed by hepatitis and hydatid cysts. The causes of kidney condemnation were nephritis, hemorrhage and calcification. Bruising was the only cause of carcass condemnation. The overall direct financial loss from organs and carcass condemnation was estimated to be 1,077,000 Ethiopian birr (ETB) or approximately 55,000 USD per annum. In conclusion, results indicated that a significant amount of revenue is lost due to carcass condemnation, and highlighted the need for strategic disease control programs, particularly for parasitic diseases.